Methacrylic acid-acrylate copolymer latex for enteric coating material and preparation method of methacrylic acid-acrylate copolymer latex
By using RAFT emulsion polymerization and the dropwise addition of specific monomers, the problems of excessive polymers and harmful emulsifiers in emulsion polymerization have been solved, achieving stable and efficient preparation of copolymer latex, which is suitable for enteric coating materials and improves the release efficiency and bioavailability of drugs in the intestine.
Patent Information
- Application Number
- CN202510809070.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-17
- Publication Date
- 2025-10-21
AI Technical Summary
In the existing technology, the preparation of methacrylic acid-acrylate copolymer latex by emulsion polymerization has problems such as a large number of aggregates, the use of harmful emulsifiers, and low efficiency of vacuum removal of unreacted monomers, which affect production efficiency and product quality.
The RAFT emulsion polymerization method is used to prepare emulsifier-free methacrylate-acrylate copolymer latex using amphiphilic macromolecular reversible addition-schistolysis and chain transfer reagents. The stability of the polymerization process and the purity of the product are ensured by specific monomer dropwise addition and vacuum removal of unreacted monomers.
This process achieves stability in the polymerization process and efficient removal of unreacted monomers from the product, reduces agglomerates, avoids the use of harmful emulsifiers, improves production efficiency and product quality, and ensures the pH responsiveness and drug protection effect of the enteric coating material.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of pharmaceutical preparations, and in particular to a methacrylic acid-acrylate copolymer latex used as an enteric coating material and a preparation method thereof. Background Art
[0002] Enteric coatings are the outer coatings of oral dosage forms and are widely used for drugs requiring precisely controlled intestinal release, such as anti-inflammatory drugs, antibacterial drugs, and some drugs used to treat intestinal diseases. Methacrylic acid-acrylate copolymer latex is a widely used pharmaceutical enteric coating material. This coating is insoluble at a specific low pH, preventing drug release in the highly acidic stomach (pH ~1). However, at higher pH values (>6), the coating dissolves, releasing the drug. This material is primarily used to protect drugs from gastric acid, ensuring intestinal release and enhancing therapeutic efficacy and bioavailability. For example, the widely used stomach medication omeprazole magnesium is easily degraded and inactivated by gastric acid. Coating the pellets with methacrylic acid-acrylate copolymer latex prevents these degradation and inactivation during oral administration. Furthermore, the coating can protect the gastric mucosa from the irritation of certain drugs.
[0003] Methacrylic acid-acrylate copolymers are formed by copolymerizing methacrylic acid and acrylate monomers in a certain proportion. Methacrylic acid-acrylate copolymers are prepared by free radical polymerization, and common processes include solution polymerization and emulsion polymerization. In practical applications, emulsion polymerization is more widely used. Emulsion polymerization uses water as the reaction medium, the system viscosity is low, the process is environmentally friendly, the reaction heat is easy to remove, and it is convenient to implement. The emulsion polymerization system usually consists of four parts, based on 100 parts (mass) of monomer, 150-250 parts of water, 2-5 parts of emulsifier, and 0.3-0.5 parts of initiator. The initiator is mostly water-soluble. When using persulfate as a single initiator, the polymerization temperature is 50-80°C. The emulsifier is mostly a mixture of anionic emulsifier and nonionic surfactant.
[0004] Due to product safety concerns, the pharmaceutical industry generally prefers to avoid the use of organic solvents in the preparation of drug dosage forms, and therefore prefers to use aqueous polymer dispersions as coating materials. Methacrylic acid-acrylate copolymer latexes produced by emulsion polymerization can be directly used to prepare enteric-coated micropellets. The enteric coating film formation principle of enteric-coated micropellets is primarily based on the ability of polymer latex to form a continuous film during the drying process. Coating materials typically include polymers and colorants, plasticizers, fillers, and more. Selecting the appropriate coating material and film-forming conditions is key to achieving the desired coating function.
[0005] Methacrylic acid-acrylate copolymer latexes (aqueous dispersions) for coating have been developed by Evonik in Germany. Brands include Eudragit L 30D-55 and Eudragit FS 30D. Sodium lauryl sulfate is used as an anionic emulsifier, and Span 80 is a nonionic emulsifier during the emulsion polymerization process. Emulsifiers are essential components of emulsion polymerization, emulsifying monomers into small droplets and forming micelles, which provide a site for initiation and polymerization. Another important function of emulsifiers is to protect the latex particles, ensuring their stable dispersion in water, thereby forming a stable latex. The choice of emulsifier has a significant impact on latex stability. An inappropriate emulsifier can cause latex particle aggregation during polymerization, which can impact production efficiency (requiring additional polymerization kettle cleaning and filtration steps) or even render the polymerization process inoperable. Sodium lauryl sulfate (SDS) is a commonly used emulsifier in emulsion polymerization. The presence of emulsifiers often adversely affects the subsequent processing and application of latex. For example, SDS is a toxic substance that irritates mucous membranes and the upper respiratory tract, is irritating to the eyes and skin, can cause allergic respiratory reactions, and ingestion can cause nausea, vomiting, and diarrhea. During the vacuum removal of small amounts of unreacted monomer, the presence of emulsifiers can easily generate large amounts of foam, reducing equipment efficiency. After the latex forms a film, the emulsifier aggregates, forming nano-domains that are susceptible to water absorption and mechanical defects.
[0006] RAFT polymerization, short for reversible addition chain transfer polymerization, is a living / controlled free radical polymerization technology whose polymer chain formation mechanism is completely different from that of traditional free radical polymerization. A RAFT agent is a compound that can undergo reversible chain transfer with free radicals. When a free radical and the RAFT agent undergo chain transfer, a dormant chain containing a RAFT group and a new free radical are generated. The dormant chain can then react with another free radical to be reactivated, allowing chain growth. RAFT polymerization has been extensively studied. RAFT emulsion polymerization has also been extensively studied, and studies have found that RAFT emulsion polymerization is prone to demulsification. This demulsification can only be avoided through specialized RAFT agent structural design and processing. Existing RAFT emulsion polymerization technology is only suitable for the polymerization of relatively hydrophobic monomers such as styrene, acrylates, methacrylates, and vinyl acetate. Its applicability to more water-soluble monomers such as methacrylic acid is unclear.
[0007] Therefore, in the field of manufacturing enteric coating materials and corresponding other pharmaceutical dosage forms, in addition to overcoming the technical problems of reducing the polymers produced during the preparation process of emulsion polymerization and avoiding the use of emulsifiers harmful to health during the preparation, it is also necessary to solve the problem of how to improve the efficiency of the vacuum removal of unreacted monomers from polymer latex. Summary of the Invention
[0008] In view of the shortcomings of the existing technology, the purpose of the present invention is to provide a methacrylic acid-acrylate copolymer latex for enteric coating materials and a preparation method thereof. The latex is prepared by a RAFT emulsion polymerization method. The product does not contain an emulsifier, the polymerization process is stable, the number of aggregates is small, and the removal of unreacted residual monomers is convenient.
[0009] The technical solutions adopted in the present invention are as follows:
[0010] The first aspect of the present invention is a methacrylic acid-acrylate copolymer latex for enteric coating materials. The latex is obtained by emulsion polymerization of a monomer mixture, wherein the monomer mixture contains 5 to 10 parts by weight of an amphiphilic macromolecular reversible addition chain-scission chain transfer agent; 35 to 55 parts by weight of a methacrylic acid monomer; and 45 to 60 parts by weight of an acrylate monomer or a mixture of an acrylate monomer and a methacrylate.
[0011] The second aspect of the present invention is to disclose a method for preparing a methacrylic acid-acrylate copolymer latex for an enteric coating material, the method comprising the following steps:
[0012] (a) adding 240 parts by weight of water and 0.2 to 5 parts by weight of an amphiphilic macromolecular reversible addition-fragmentation chain transfer agent to a reactor, stirring and mixing, passing nitrogen gas until the air is completely replaced, and heating to 40 to 90° C.;
[0013] (b) adding 1.68 parts by mass of an initiator, and adding dropwise 35 to 55 parts by mass of a methacrylic acid monomer and 45 to 60 parts by mass of an acrylate monomer at a constant rate. After the monomer addition is complete, the reaction is continued for 1 to 5 hours;
[0014] (c) Subsequently, unreacted monomers are removed under vacuum to obtain a methacrylic acid-acrylate copolymer latex.
[0015] Specifically, the general chemical structure of the amphiphilic macromolecular reversible addition-fragmentation chain transfer reagent is:
[0016]
[0017] Among them, the Z group is selected from: phenyl, benzyl, methyl, ethyl, propyl, isopropyl, butyl and its isomers, pentyl and its isomers, ethoxy, methoxythiol, ethylmercapto, isopropylmercapto, butylmercapto, C12 mercapto; the R group is selected from: 1-methylbenzyl, 1,1-dimethylbenzyl, isopropanoic acid, 2-diisobutyric acid, 2-isobutyronitrile, cyanopentanoic acid, 3-benzoic acid; the lipophilic monomer includes acrylates and methacrylates; the hydrophilic monomer is methacrylic acid, and the ratio of n to m is 3 to 7; the molecular weight of the amphiphilic macromolecular reversible addition chain scission chain transfer reagent is 800 to 10,000.
[0018] Specifically, the acrylate monomer includes one or more of ethyl acrylate, methyl acrylate, and methyl methacrylate; and the initiator is persulfate, or azo and its derivatives.
[0019] The beneficial effects of the present invention are as follows:
[0020] This invention utilizes a specially structured amphiphilic RAFT agent, combined with a unique monomer addition strategy, to achieve RAFT emulsion copolymerization of methacrylic acid and (meth)acrylates. This results in a stable polymerization process, minimal demulsification and coagulant formation, and reduced post-production reactor cleaning effort. The copolymer latex contains no harmful emulsifiers, and vacuum removal of unreacted monomers without foaming, facilitating post-polymerization processing. The copolymer latex can be used in enteric coatings and exhibits excellent pH responsiveness, protecting omeprazole magnesium from damage at pH 1 and 5.0 and allowing near-complete release of the drug at pH 6.2. DETAILED DESCRIPTION
[0021] Here, exemplary embodiments will be described in detail. The implementation methods described in the following exemplary embodiments do not represent all implementation methods consistent with the present application.
[0022] Example 1
[0023] In a 1L five-necked flask reactor, add 55.5g of methacrylic acid, 65.2g of ethyl acrylate, 0.8g of sodium lauryl sulfate, 2.8g of polyoxyethylene sorbitan monooleate, and 286.0g of deionized water, respectively. Dissolve and stir. Set the mechanical stirring blade speed to 250rpm and purge with nitrogen to deoxygenate for at least 1 hour. Then heat the system in a water bath to 70°C. Add a pre-prepared initiator solution (containing 2.0g of sodium persulfate and 9.0g of deionized water) and start the reaction. After 6 hours of reaction, reduce the temperature to room temperature, stop nitrogen purging and stirring, and filter the product latex through a 200-mesh filter and pour into a wide-mouth plastic bottle.
[0024] Example 2
[0025] (1) In a 1 L five-necked flask reactor, 0.7 g of sodium lauryl sulfate, 2.5 g of polyoxyethylene sorbitan monooleate, 4.5 g of methacrylic acid, 5.2 g of ethyl acrylate, and 286.0 g of deionized water were added and dissolved with stirring. The mechanical stirring blade was set to 250 rpm and nitrogen was purged for deoxygenation for at least 1 hour. The system was then heated in a water bath to 70°C.
[0026] (2) Dissolve 0.5 g of sodium persulfate in 5.0 g of deionized water and stir to prepare an initiator solution. After nitrogen purging is complete, maintain the nitrogen purging state and add the initiator sodium persulfate solution. React for 30 minutes to obtain a seed emulsion.
[0027] (3) The monomer mixture required before the experiment was prepared in a 250 mL round-bottom flask, and 51.0 g of methacrylic acid, 60.0 g of ethyl acrylate, 0.1 g of sodium lauryl sulfate, 0.3 g of polyoxyethylene sorbitan monooleate and 10.0 g of deionized water were added and magnetic stirring was performed.
[0028] (4) After the seed emulsion was synthesized, the monomer mixture was added dropwise to a 1 L flask via a syringe pump at a flow rate of 0.6 mL / min for a total of approximately 3.8 h. After the monomer addition was complete, the reaction was continued for 0.5 h to increase the monomer conversion.
[0029] (5) After step (4), the reaction mixture was vacuumed for 2 hours at a vacuum degree of -0.07 MPa to remove unreacted monomers.
[0030] (5) After the reaction is completed, the temperature is lowered to room temperature, the nitrogen flow and stirring are stopped, and the product latex is filtered through a 200-mesh filter and poured into a wide-mouth plastic bottle.
[0031] Latex alkali solubility test
[0032] Take 5 grams of latex, slowly add 1M NaOH aqueous solution to the latex while stirring, use a magnetic stirrer to stir slowly, and observe its dissolution under alkaline conditions (pH>6.2).
[0033] Example 3
[0034] In a 1L five-necked flask reactor, 55.5g of methacrylic acid, 65.2g of ethyl acrylate, 3.6g of amphiphilic RAFT agent (amphiphilic macromolecular reversible addition scission chain transfer agent) C were added. 12 H 25 SS=CS-EA5-b-MAA 20 -CH3COOH and 286.0g deionized water, dissolve and stir, set the mechanical stirring blade speed to 250rpm, and purge with nitrogen to deoxygenate for more than 1h. Then heat the system in a water bath to 70°C. Add the pre-made initiator solution (containing 2.0g sodium persulfate and 9.0g deionized water) and start the reaction. After 6h of reaction, reduce the temperature to room temperature, stop nitrogen purging and stirring, and filter the product latex through a 200-mesh filter and pour into a wide-mouth plastic bottle.
[0035] Example 4
[0036] 3.6 g of amphiphilic RAFT agent C was added to a 1 L five-necked flask reactor. 12 H 25 SS=CS-EA5-b-MAA 20-CH3COOH and 286.0g deionized water, dissolve and stir, set the speed of the mechanical stirring blade to 250rpm, and pass nitrogen to deoxygenate for more than 1h. Then heat the system in a water bath to 70°C. Add the pre-made initiator solution (containing 2.0g sodium persulfate and 9.0g deionized water). Mix 55.5g methacrylic acid and 65.2g ethyl acrylate evenly, and add the monomer mixture dropwise to the reactor at a flow rate of 0.6mL / min through a syringe pump. After the addition is complete, continue the reaction for 2 hours, reduce the temperature to room temperature, stop passing nitrogen and stirring, and filter the product latex through a 200-mesh filter and pour into a wide-mouth plastic bottle for later use.
[0037] Example 5
[0038] 1.8 g of amphiphilic RAFT agent C was added to a 1 L five-necked flask reactor. 12 H 25 SS=CS-EA3-b-MAA 20 -CH3COOH and 286.0g deionized water, dissolve and stir, set the speed of the mechanical stirring blade to 250rpm, and pass nitrogen to deoxygenate for more than 1h. Then heat the system in a water bath to 70°C. Add the pre-made initiator solution (containing 2.0g sodium persulfate and 9.0g deionized water). Mix 55.5g methacrylic acid and 65.2g ethyl acrylate evenly, and add the monomer mixture dropwise to the reactor at a flow rate of 0.6mL / min through a syringe pump. After the addition is complete, continue the reaction for 2 hours, reduce the temperature to room temperature, stop passing nitrogen and stirring, and filter the product latex through a 200-mesh filter and pour into a wide-mouth plastic bottle for later use.
[0039] Example 6
[0040] 3.6 g of amphiphilic RAFT agent C was added to a 1 L five-necked flask reactor. 12 H 25 SS=CS-EA7-b-MAA 27 -CH3COOH and 286.0g deionized water, dissolve and stir, set the speed of the mechanical stirring blade to 250rpm, and pass nitrogen to deoxygenate for more than 1h. Then heat the system in a water bath to 70°C. Add the pre-made initiator solution (containing 2.0g sodium persulfate and 9.0g deionized water). Mix 55.5g methacrylic acid and 65.2g ethyl acrylate evenly, and add the monomer mixture dropwise to the reactor at a flow rate of 0.6mL / min through a syringe pump. After the addition is complete, continue the reaction for 2 hours, reduce the temperature to room temperature, stop passing nitrogen and stirring, and filter the product latex through a 200-mesh filter and pour into a wide-mouth plastic bottle for later use.
[0041] Example 7: 3.6 g of amphiphilic RAFT agent C and 3.6 g of amphiphilic RAFT agent C were added to a 1 L five-necked flask reactor. 12 H 25 SS=CS-EA5-b-MAA 20 -CH3COOH and 286.0g deionized water, dissolve and stir, set the speed of the mechanical stirring paddle to 250rpm, and pass nitrogen to deoxygenate for more than 1h. Then heat in a water bath to raise the system temperature to 70°C. Add prefabricated initiator solution (containing 2.0g sodium persulfate, 9.0g deionized water). 55.5g methacrylic acid, 32.6g methyl methacrylate and 32.6g ethyl acrylate are mixed uniformly, and the monomer mixture is added dropwise to the reactor at a flow rate of 0.6mL / min by a syringe pump. After the addition is complete, the reaction is continued for 2 hours, the temperature is lowered to room temperature, nitrogen is stopped and stirring is stopped, and the product latex after discharging is filtered through a 200-mesh filter screen and poured into a wide-mouthed plastic bottle for standby use. As shown in Table 1 (Summary of Emulsion Polymerization Results) and Table 2 (Foaming and Alkali Solubility Characteristics of Copolymer Latex):
[0042] Table 1
[0043]
[0044]
[0045] Table 2
[0046] Example Polymerization process Foaming characteristics Alkali solubility (pH>6.2) 1 Batch polymerization Easy to foam Gelation, white insoluble 2 Semi-continuous polymerization Easy to foam Clear, transparent, easy to flow 3 Intermittent, RAFT No bubbles Translucent, viscous fluid 4 Semi-continuous, RAFT No bubbles Clear, transparent, easy to flow 5 Semi-continuous, RAFT No bubbles Clear, transparent, easy to flow 6 Semi-continuous, RAFT No bubbles Clear, transparent, easy to flow 7 Semi-continuous, RAFT No bubbles Clear, transparent, easy to flow
[0047] Latex alkali solubility test: Take 5 grams of latex, slowly add 1M NaOH aqueous solution to the latex while stirring, use a magnetic stirrer to stir slowly, and observe its dissolution under alkaline conditions (pH>6.2).
[0048] Example 8
[0049] Enteric-coated pellets were coated using a FLZB-3.0 experimental multifunctional fluidized bed. Plasticized methacrylic acid-ethyl acrylate copolymer latex was selected as the enteric coating material. Enteric-coated pellets were prepared using a fluidized bed bottom spray coating process. Sucrose pellets were used as the starting material, and the drug-loading layer, isolation layer, and enteric coating were applied in sequence.
[0050] First, the binder is dissolved in continuously stirred purified water. Once completely dissolved, the drug (13 wt% omeprazole magnesium) and a binder (2 wt% hydroxypropyl methylcellulose) are added. After homogenization, a uniform slurry with a solids content of 15 wt% is obtained. The drug is then coated onto the surface of the sucrose core using fluidized bed technology, with a weight gain of 20% to 25%. Subsequently, in the preparation of the isolation layer micropellets, the binder (3 wt% hydroxypropyl cellulose) is also added to purified water, stirred until completely dissolved, and then an anti-adherent (7 wt% talc) is added. After homogenization, a slurry with a solids content of 10% is obtained, which is then used to coat the drug-loaded micropellets with an isolation layer, with a weight gain of 20% to 25%. Finally, in the preparation of enteric-coated micropellets, methacrylic acid-(meth)acrylate copolymer emulsion (50 wt%) and plasticizer (1.5 wt% triethyl citrate) were sequentially added to an appropriate amount of purified water, stirred evenly to obtain a slurry with a solid content of 15 wt% for enteric coating of the isolation layer micropellets, with a weight gain range of 25% to 30%.
[0051] The drug encapsulated in the enteric-coated micropellets—omeprazole magnesium—is a widely used proton pump inhibitor used to treat digestive system diseases such as gastric ulcers. Its chemical structure consists of a benzimidazole ring and a pyridine ring connected by a sulfoxide group. Omeprazole magnesium is unstable in contact with acidic media, resulting in significant drug degradation in the stomach, thereby reducing its bioavailability. Furthermore, the pharmacological effects of omeprazole magnesium in the digestive tract can lead to an increase in gastric pH, which further affects its stability. Therefore, the acid resistance of the enteric coating film is a key factor in ensuring drug effectiveness and therapeutic efficacy. The methacrylic acid-ethyl acrylate copolymer (10 wt% (polymer dry basis) TEC, 50 mol% MAA) prepared in Example 2-7 was selected as the enteric material. Under the same enteric weight gain premise (25% to 30%), the acid resistance of the micropills in buffer solutions with pH values of 1.0 and 5.0 (paddle method - 100 rpm - 2h) was used as the evaluation index to investigate its effect on the performance of the formulation. The results are shown in Table 3 (acid resistance data of micropills in pH 1.0 solution) and Table 4 (acid resistance data of micropills in pH 5.0 solution).
[0052] Table 3
[0053]
[0054] Note: *Acid resistance is characterized by the residual content of pellets after the test.
[0055] The coated pellets prepared from the materials of Examples 2-7 have good acid resistance at a pH of 1.0 (this condition simulates the gastric acid condition when fasting), indicating that the enteric coating can protect the coated drug under this condition.
[0056] Table 4
[0057]
[0058] Note: *Acid resistance is characterized by the residual content of pellets after the test.
[0059] The coated micropellets prepared from the materials of Examples 4-7 have good acid resistance under the condition of pH 5.0 (which simulates the gastric acid environment under full stomach conditions), indicating that the enteric coating can play a role in protecting the coated drug under these conditions. The coated micropellets prepared from the materials of Examples 2-3 have low acid resistance and cannot effectively protect the drug.
[0060] Example 9
[0061] The pellets prepared in Example 8 were subjected to a dissolution test in a pH 6.2 phosphate buffer solution for 30 minutes. The results are shown in Table 5. The dissolution rate is the percentage of drug dissolved. The dissolution rate of the pellets in a pH 6.2 phosphate buffer solution is shown in Table 5:
[0062] Table 5
[0063] Enteric-coated materials Dissolution rate, % Example 3 93 Example 4 94 Example 5 92 Example 6 93 Example 7 94
[0064] Table 5 shows that the coated pellets prepared from the materials of Examples 3-7 can be effectively released under the intestinal pH environment.
[0065] Those skilled in the art will readily conceive of other embodiments of the present application after considering the specification and practicing the contents disclosed herein. This application is intended to cover any variations, uses, or adaptations of the present application that follow the general principles of this application and include common knowledge or customary techniques in the art that are not disclosed in this application.
[0066] It will be understood that the present application is not limited to what has been described above and that various modifications and changes may be made without departing from the scope thereof.
Claims
1. A methacrylic acid-acrylate copolymer latex for enteric coating material, characterized in that: The latex is obtained by emulsion polymerization of a monomer mixture, wherein the monomer mixture contains 5 to 10 parts by weight of an amphiphilic macromolecular reversible addition chain-scission chain transfer agent; 35 to 55 parts by weight of a methacrylic acid monomer; and 45 to 60 parts by weight of an acrylate monomer or a mixture of an acrylate monomer and a methacrylate.
2. A method for preparing the methacrylic acid-acrylate copolymer latex for enteric coating material according to claim 1, characterized in that: The method comprises the following steps: (a) adding 240 parts by weight of water and 0.2 to 5 parts by weight of an amphiphilic macromolecular reversible addition-fragmentation chain transfer agent to a reactor, stirring and mixing, passing nitrogen gas until the air is completely replaced, and heating to 40 to 90° C.; (b) adding 1.68 parts by mass of an initiator, and adding dropwise 35 to 55 parts by mass of a methacrylic acid monomer and 45 to 60 parts by mass of an acrylate monomer at a constant rate. After the monomer addition is complete, the reaction is continued for 1 to 5 hours; (c) Subsequently, unreacted monomers are removed under vacuum to obtain a methacrylic acid-acrylate copolymer latex.
3. The preparation method according to claim 2, characterized in that The general chemical structure formula of the amphiphilic macromolecular reversible addition-fragmentation chain transfer reagent is: Among them, the Z group is selected from: phenyl, benzyl, methyl, ethyl, propyl, isopropyl, butyl and its isomers, pentyl and its isomers, ethoxy, methoxythiol, ethylmercapto, isopropylmercapto, butylmercapto, C12 mercapto; the R group is selected from: 1-methylbenzyl, 1,1-dimethylbenzyl, isopropanoic acid, 2-diisobutyric acid, 2-isobutyronitrile, cyanopentanoic acid, 3-benzoic acid; the lipophilic monomer includes acrylates and methacrylates; the hydrophilic monomer is methacrylic acid, and the ratio of n to m is 3 to 7; the molecular weight of the amphiphilic macromolecular reversible addition chain scission chain transfer reagent is 800 to 10,000.
4. The preparation method according to claim 2, characterized in that The acrylic acid ester monomer includes one or more combinations of ethyl acrylate, methyl acrylate, and methyl methacrylate; the initiator is persulfate, or azo and its derivatives.
